EVALUASI IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN SIMULASI DIGITAL DI SMK NEGERI KOTA PADANG - Elqie Melati Sukma Syah; Fahmi Rizal; Hansi Effendi (Jurnal Informatika, 2021)
Based on preliminary observations, the implementation of Curriculum 2013 on digital simulation subjects is suspected to still experience obstacles. Obstacles that occur related to the elements in the implementation of Curriculum 2013 namely human resources (teachers and students) and facilities infrastructure. The purpose of this study is the evaluation of Curriculum 2013 implementation using Context-Input-Process-Product (CIPP) model. This research is a program evaluation study with CIPP evaluation model. The method used is Mixed Method with concurent triangulation design. Quantitative data collection techniques in the form of questionnaires, while qualitative data in the form of interviews, observation and documentation. The population was taken from SMK Negeri Kota Padang using the curriculum 2013and the sample was taken randomly by Simple Random Sampling method. Quantitative data were analyzed by scoring techniques and qualitative data were analyzed by analytical techniques according to Miles and Huberman. The results showed that the implementation of Curriculum 2013 on Digital Simulation Subjects at SMK Negeri 2 Padang, SMK Negeri 8 Padang, and SMK Negeri 9 Padang stated very well with the results of quantitative data analysis declared valid and reliable, and supported with the results of qualitative data analysis. Based on the research findings of quantitative and qualitative combination methods it is recommended that the 2013 Curriculum implementation be mutually reinforcing and can be continued for the next year by making improvements.